Utilization of Cotton Waste from PT Sri Rejeki Isman Tbk. Spinning Division as Basic Material for White Oyster Mushroom (Pleurotus ostreatus) Planting Media - Tasya Sienita; Makhmudun Ainuri; Moh. Wahyudin (Agroindustrial Journal, 2022)
There are five types of cotton waste produced by the Spinning Division of PT. Sri Rejeki Isman Tbk: dropping, flat strip recyclean, flat strip c, air waste, and fan open end, which has a smaller trash content. The research objective is to determine the potential utilization of cotton waste as the basic material for white oyster mushroom planting media, to determine effect of planting media formula on the growth of white oyster mushroom, and to determine the best formula for white oyster mushroom planting media. Utilization of cotton waste are examined by 5 formulas: control with 100% sengon wood powder + 200 gram bran + 10 gram lime (S0), 50% dropping + 50% sengon wood powder + 200 gram bran + 10 gram lime (S1a), 75% dropping + 25% sengon wood powder + 200 gram bran + 10 gram lime (S1b), 50% fan open end + 50% sengon wood powder + 200 gram bran + 10 gram lime (S2a) and 75% fan open end + 25% sengon wood powder + 200 gram bran + 10 gram lime (S2b). This study uses a 5x3 Completely Randomized Design (CRD 5x3) and is then analyzed using the One Way Anova test and the Least Significant Difference (LSD) test. The best formula was chosen for planting media based on the highest score in Zero-One Integer Programming. Parameters observed on the planting media are changes in the content of cellulose and lignin, while on the fungal growth is the form of mycelium fulfillment time; the number of fruit bodies; hood width; wet weight, and stem length. This study indicates that cotton waste can be used as a base material for white oyster mushroom planting media, where the best formula is S2b. During fungal growth, in the planting media with formula S2b, cellulose degradation occurs from 66.7% to 60.8%, and lignin degradation occurs from 10.5% to 6.6%. In addition to the media, formula S2b produces mushrooms with growth characteristics including mycelium fulfillment time of 28.33±1.53 days, the number of fruit bodies 17.67±8.96, hood width 5.76±0.87 cm, wet weight 143.33±26.27 grams, and stalk length 4.52±0.55 cm.